The impact of family income and household resources on secondary students’ English achievement: A mediation analysis of educational resource access - Yafen, Huang; Nathan, Sanmuga; Ramachandran, Sailaja (Edelweiss Applied Science and Technology, 2026)
This study examines how family capital influences middle school students’ foreign language achievement amidst urban-rural educational stratification in Central China. Utilizing survey data from 465 eighth-grade students in Jiangxi Province, the study conducts empirical tests through structural equation modeling (SEM) and Bootstrap procedures. Path and mediation analyses indicate that both fluid family income and fixed family resources exert a fully mediated influence on English academic performance. This effect is indirectly realized as a marginal academic dividend solely through the institutional bridge of Educational Resource Access (ERA). Crucially, after controlling for equal resource access, family income exhibits a significant inhibitory effect on English grades. This negative impact reflects the capital anxiety and financial misallocation experienced by high-income families under China’s “Double Reduction” policy. Ultimately, this study enriches empirical evidence for capital reproduction theory within language acquisition and offers policy insights to interrupt the transmission of family socioeconomic background into micro-level academic disparities.